2018
DOI: 10.1101/388710
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Allele frequency dynamics in a pedigreed natural population

Abstract: A central goal of population genetics is to understand how genetic drift, natural selection, and gene flow shape allele frequencies through time. However, the actual processes underlying these changes -variation in individual survival, reproductive success, and movement -are often difficult to quantify. Fully understanding these processes requires the population pedigree, the set of relationships among all individuals in the population through time. Here, we use extensive pedigree and genomic information from … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
(29 reference statements)
1
11
0
Order By: Relevance
“…They attributed this result to the relatively few adults which succeed in breeding every year (low effective population size), even though large number of adult salmons reached the hatchery. Similar pattern was shown by Chen et al 43 using a detailed long term (23 years) pedigree of Florida Scrub-Jays ( Aphelocoma coerulescens ) and SNPs data. They showed that annual allele frequency variations can be explained by change in survival and reproductive success of breeders, and that the contribution of gene flow is small.…”
Section: Discussionsupporting
confidence: 85%
“…They attributed this result to the relatively few adults which succeed in breeding every year (low effective population size), even though large number of adult salmons reached the hatchery. Similar pattern was shown by Chen et al 43 using a detailed long term (23 years) pedigree of Florida Scrub-Jays ( Aphelocoma coerulescens ) and SNPs data. They showed that annual allele frequency variations can be explained by change in survival and reproductive success of breeders, and that the contribution of gene flow is small.…”
Section: Discussionsupporting
confidence: 85%
“…Other factors such as such matting pattern, random genetic drift, individual survival, reproductive success, and migration also generate genetic variation in a population (Chen et al 2019). In the current study we sequenced only 40 goats, it would have an effect on the genotypic and allelic frequencies we observed; hence, large population-scale research is required to confirm the genotypic and allelic frequencies in Black Bengal goat of Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…In the most extreme case, shrinkage , we found that a decline in π may not be detectable until >100 generations after range contraction despite a >80% loss in suitable habitat ( Figure 3 ). This finding demonstrates a pressing need for the field of conservation genetics to adopt more sensitive measures of population health than π, such as length of identity-by-descent (IBD) tracts (see Chen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%